Factors Affecting Purchase Intention for Airline Services A Comparison Study between Thai Smile Air and Thai AirAsia, Bangkok-Krabi Flights - เชียรวัฒนสุข, กฤษดา; ไกรเลิศ, ปิยวรรณ (Business Administration and Management Journal Review, 2016)
This research was conducted to investigate the factors that affected the purchase intention for the airline services: a comparison study between the Thai Smile Air and the Thai Air Asia, Bangkok-Krabi Flights. The data were collected from 225 Thai Smile Air passengers and 225 Thai Air Asia passengers at Suvarnabhumi Airport and Krabi Airport as the study samples. Percentage, Mean, Standard Deviation, One-way ANOVA, and Multiple Regression Analysis were employed for data analysis. Study results revealed that factors affecting the intention to use the Thai Smile Air services included age group between 51 and 60 years old (β = 0.125), occupation i.e. housekeeper/retiree (β = -0.111) and the service marketing mix factors of the Thai Smile Air in the aspects of product and service (= 0.218), promotion (β = 0.445), and personnel and employees (β = 0.204). Factors affecting the intention to use Thai Air Asia service included education level which is higher than bachelor degree (β = 0.226) and service marketing mix factors of the Thai Air Asia in the aspects of price (β = 0.176). In addition, the study findings also indicated that the service application behavior on reservation methods and payment channel had differently influenced on the overall intention to use the services of the Thai Smile Air. Lastly, the service application date had differently influenced on the overall intention to use the services of the Thai AirAsia.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">